Asuhan Keperawatan Pada An. R Dengan Gangguan Sistem Pencernaan: Dispepsia Di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Afiati Amelia Rosadi; Esti Nur Janah; Wawan Hediyanto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Dyspepsia is a condition or collection of symptoms such as a feeling of discomfort in the upper part of the stomach as well as subjective complaints in the form of nausea, vomiting, burning sensation, bloating in the upper digestive tract, feeling full quickly, feeling full in the stomach after eating and also belching (Ashari , Yuniati & Murti, 2021).